Analysis of strut forces for braced excavations in sand - Chee, Benjamin Jin Sheng (2014)
Most numerical studies published for braced excavations involve soft to stiff clays, but few studies involve braced excavations in sand. Therefore this study looks into the numerical analysis of strut forces for braced excavations in sand via the finite element method. Two dimensional (2D) finite element analysis was carried out using PLAXIS 2D to compare strut forces obtained from numerical analysis against the semi-empirically derived apparent pressure diagram. Parametric studies were also done to investigate the effects of wall stiffness, depth from base of excavation to hard stratum, D/T ratio (D=wall embedment depth, T=depth of base of excavation to hard stratum), sand stiffness, and sand friction angle on strut forces. The results show that the apparent pressure diagram generally overestimates strut forces for the upper two struts and underestimates strut forces for the lower two struts. The parametric studies conducted show that increasing wall stiffness does not lead to increased strut forces. Lower strut forces are obtained when the depth from the base of excavation to hard stratum is increased. For a constant D/T ratio, higher magnitudes of both the D and T values will result in lower strut forces. However, when different D/T ratios are used, it was found that lower D/T ratios lead to lower strut forces. For a constant T, results show that increasing the wall embedment depth (D) has no impact on strut forces. Increasing sand stiffness alone did not result in significantly lower strut forces. However, increasing sand friction angle, which brings about a higher sand stiffness, results in significantly lower strut forces.